Five Parameter PV Model Extraction and Improvement Based on Experimental Data - Ali Mahmood, Humada; Hojabri, Mojgan; M. H., Sulaiman; Saad, Mekhilef (2016)
This paper presents a new approach of the single diode five parameters model extraction and performance evaluation. The proposed model is capable of analytically describing the I–V and P–V characteristics of a PV module in different conditions. The PV parameters identify, mainly, the accuracy of any PV model. The proposed model constructed in a method to be in a sounds level of accuracy and far from complication. In term of accuracy, different evaluation criteria have being used in this study, and results of all criteria showed merit level of accuracy comparison to those in the compared models. In addition, the performance of the five parameters has been improved and this improvement showed in the I–V and P–V characteristics. Effect of these five parameters on all of the maximum power point (MPP), short circuit current (Isc), and open circuit voltage (Voc) also showed in the results. The outcomes of this study could help in improving the total PV system performance and could be a guide for method of extraction the five parameters model, since it dependent mainly on real results.